Gender composition and conflicts of interest in the financial industry: Evidence from analysts’ target price optimism - Charalambous, Andria; Duboisée de Ricquebourg, Alan; Scarlat, Elvira; Shields, Karin (Elsevier, 2025)
A barrage of regulatory requirements has been issued to increase the impartiality of sell-side analysts’ research reports and create a wall between equity research and investment banking departments. Yet studies suggest a persistent organizational culture within the profession that encourages optimistically biased research reports for current and potential investment banking clients. To examine potential solutions to this issue, we focus on sell-side analysts’ target price optimism and find that analysts at brokerages with higher female representation issue significantly less optimistic target prices, especially when they face incentives to inflate forecasts due to their brokerage’s affiliation to the firm being analyzed. To identify the mechanism behind this result, we explore analysts’ optimism bias in situations when mergers between banks change gender composition in a way that is exogenous to the analysts, as well as when analysts voluntarily switch between brokerages with different gender compositions. The results of these analyses, along with a lag and forward test of the relation between the female proportion of analysts and optimism bias, indicate that gender composition plays a significant role in shaping brokerage culture. We rule out that results are driven by the gender of the individual analyst and confirm our results’ robustness to various specifications. Our findings suggest the potential for gender composition of the workforce to aid self-regulation in the financial industry.
Keywords: 53 Ciencias Económicas; ODS 5 - Igualdad de género; Financial analysts; Optimism; Target prices; Gender composition; Conflicts of interest; Ethicality